Dark-field X-ray microscopy reveals mosaicity and strain gradients across sub-surface TiC and TiN particles in steel matrix composites. (October 2020) - Hlushko, K.; Keckes, J.; Ressel, G.; Pörnbacher, J.; Ecker, W.; Kutsal, M.; Cook, P.K.; Detlefs, C.; Yildirim, C.
Abstract: Residual strain gradients and crystallographic mosaicity across embedded ceramic particles within metal-matrix composites have remained experimentally inaccessible. In this work, we use synchrotron dark-field X-ray microscopy to characterize strain and orientation gradients across ~20 µm large TiC and TiN particles embedded in a steel matrix annealed at 480 and 600 °C. The results document gradual crystallographic orientation changes across the particles and the presence of sub-grains, in contrast to electron backscatter diffraction data. These gradients appear, however, not directly correlated with the observed strain gradients, which are attributed mainly to the different strain states within particles' interiors and envelopes. Graphical abstract: Image, graphical abstract